HUBUNGAN MUTU PELAYANAN DENGAN KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT IBU DAN ANAK AISYIYAH SAMARINDA TAHUN 2024 - Wardani, Citra Rizki; Adrianto, Ratno; Sumarni, Sumarni; AR, Chaerunnisa; Elvira, Vivi Filia (Jurnal Manajemen Kesehatan Indonesia, 2025)
Data on outpatient visits at Aisyiyah Samarinda Mother and Child Hospital in 2022-2024 where the data for 2022 is 9,839 visitors, in 2023 there has been an increase where the number of patient visits amounted to 18,689 visitors, and in 2024 until October there was a decrease where the number of patient visits amounted to 15,783 visitors. This study aims to determine the relationship between service quality and outpatient satisfaction at Aisyiyah Samarinda Maternal and Child Hospital in 2024. This type of research is quantitative research using cross sectional studies. The number of samples was 132 respondents using the purposive sampling technique. Data analysis uses univariate and bivariate analysis with chi squared test. The results showed that there was a relationship between technical competence (ρ = 0.025), access to services (ρ = 0.001), and comfort (0.008) with outpatient satisfaction at RSIA Aisyiyah Samarinda. Meanwhile, there was no relationship between human relationships (ρ = 0.916) and outpatient satisfaction at RSIA Aisyiyah Samarinda. So it can be concluded that there is a relationship between technical competence, access to services, and comfort with patient satisfaction. However, there was no relationship between human relationships and outpatient satisfaction at RSIA Aisyiyah Samarinda.